1998
DOI: 10.1021/jo980846+
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Benzene-Centered Porphyrin Trimers and a Dendritic Porphyrin Hexamer

Abstract: Rigid, star-shaped D 3-symmetric arrays have been synthesized in which three porphyrin macrocycles are attached to the 1, 3, and 5 positions each of a benzene core through linkers consisting of collinear repetitive phenylethynyl units. Using the same methodology, a dendridic porphyrin hexamer having an external diameter of ca. 10 nm has been also obtained. By successive substitution of the three benzene positions, both a porphyrin trimer, the three linkers of which are of different length, and a starlike porph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 47 publications
1
72
0
2
Order By: Relevance
“…2-(3,5-Diiodophenyl)-1-(trimethylsilyl)acetylene (4) [16] was selected for the convergent synthesis. This monomer is easily prepared [16] in good yield from 1,3,5-triiodobenzene.…”
Section: Preparation Of Phenylacetylene Dendrimers With Peripheral DImentioning
confidence: 99%
“…2-(3,5-Diiodophenyl)-1-(trimethylsilyl)acetylene (4) [16] was selected for the convergent synthesis. This monomer is easily prepared [16] in good yield from 1,3,5-triiodobenzene.…”
Section: Preparation Of Phenylacetylene Dendrimers With Peripheral DImentioning
confidence: 99%
“…Sonogashira coupling of methyl 3-bromo-6-iodobenzoate 17 and trimethylsilylacetylene followed by basic removal of the trimethylsilyl (TMS) group gave arylacetylene 18. The second Sonogashira coupling with iodobenzene or 3-iodo-1-methylthiobenzene 14,15) provided 1,2-diarylacetylenes 19. While hydrogenation of 19a smoothly gave ester 20a with catalytic platinum oxide under atmospheric pressure, reduction of 19b required high-pressure (70 atm) conditions for the high-yielding process.…”
Section: )mentioning
confidence: 99%
“…In the covalently linked porphyrin arrays, a variety of linkages such as ethyne [36,37], polyyne [38][39][40], ethylene [41], alkane [42,43] and aromatic entities [44][45][46] have been used to bridge the individual porphyrins. Lindsey et al have reported the synthesis of numerous phenylene-and diphenyl ethynyl-bridged multiporphyrins for mimicking the biological light-harvesting antenna systems and their photo physical properties have been studied [46][47][48].…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%